2016
DOI: 10.1038/aps.2015.146
|View full text |Cite|
|
Sign up to set email alerts
|

Ophiopogonin D maintains Ca2+ homeostasis in rat cardiomyocytes in vitro by upregulating CYP2J3/EETs and suppressing ER stress

Abstract: Aim: CYP2J3 in myocardium metabolizes arachidonic acid to 4 regioisomeric epoxyeicosatrienoic acids (EETs), which have diverse biological activities in rat heart. In this study we examined whether CYP2J3 was involved in cardioprotective effects of ophiopogonin D (OPD), a steroidal glycoside isolated from Chinese herb Radix ophiopogonis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…These protective effects are thought to be mediated through the role of EETs in increasing the expression of antioxidant enzymes resulting in reduced levels of reactive oxygen species, thus preventing SERCA oxidation [130]. Likewise, the overexpression of the CYP2J2, a predominant epoxygenases responsible for the biosynthesis of EETs in heart and endothelial cells suppressed ER stress in mice cardiomyocytes and protected against cardiac failure by maintaining intracellular Ca 2+ homeostasis and SERCA2a expression and activity [131]. In line with these findings, overexpression of the rat homologue CYP2J3 prevented high fat diet-induced ER stress in adipose tissue of rats and inhibited thapsigargin-induced ER stress in differentiated 3T3-L1 mouse adipocytes [132].…”
Section: Modulation Of Er Stress By Soluble Epoxide Hydrolasementioning
confidence: 99%
“…These protective effects are thought to be mediated through the role of EETs in increasing the expression of antioxidant enzymes resulting in reduced levels of reactive oxygen species, thus preventing SERCA oxidation [130]. Likewise, the overexpression of the CYP2J2, a predominant epoxygenases responsible for the biosynthesis of EETs in heart and endothelial cells suppressed ER stress in mice cardiomyocytes and protected against cardiac failure by maintaining intracellular Ca 2+ homeostasis and SERCA2a expression and activity [131]. In line with these findings, overexpression of the rat homologue CYP2J3 prevented high fat diet-induced ER stress in adipose tissue of rats and inhibited thapsigargin-induced ER stress in differentiated 3T3-L1 mouse adipocytes [132].…”
Section: Modulation Of Er Stress By Soluble Epoxide Hydrolasementioning
confidence: 99%
“…In our earlier studies, we described for the first time the activation of CYP2J3 by OP-D in cultured H9c2 cells. We demonstrated that OP-D suppressed drug-induced endoplasmic reticulum stress by upregulating the levels of CYP2J3/EET in cardiomyocytes [18]. Additionally, we found that OP-D exerts endotheliumprotective effects via the CYP2J2/EET/PPARα signaling pathway in HUVECs [19].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 69%
“…Ginsenoside Re has a negative effect on cardiac contractility and autorhythmicity by altering cardiac electrophysiological properties [ 58 , 59 ]. In addition, Ophiopogonin D from Ophiopogon japonicas reduces intracellular Ca 2+ overload and suppressed ER stress and stress-mediated apoptosis in cardiomyocytes [ 60 ]. Other important compounds in ESMS, Schizandrol A and Schisandrin B, protect against myocardial injury by acting against oxidative damage [ 18 , 61 ].…”
Section: Discussionmentioning
confidence: 99%